Earthquake performance of reinforced-concrete (RC) frame buildings using nonlinear pushover method - Tas, Omer Faruk; Sayin, Erkut (Techno-Press, 2026)
This study assessed the seismic performance of four newly designed reinforced concrete (RC) frame buildings with identical layouts and varying heights (3, 5, 7, and 10 storeys) using the nonlinear pushover analysis method. The buildings were modelled in SAP2000 in accordance with the Turkish Building Earthquake Code 2018 (TBEC-2018), accounting for the seismic conditions in Elaz & imath;& gbreve;, Turkey. Plastic hinge properties were specified as user-defined components based on moment-curvature relationships generated from XTRACT software. Analysis results demonstrated that plastic hinges began to form at the beam ends in the lower storeys, then spread towards the upper storeys, and that the lower-storey columns began to yield. The beams sustained more damage than the columns, which is consistent with the designed ductile behaviour mechanism, in which beams are intentionally detailed to form plastic hinges before columns. This result confirmed the suitability of the plastic hinge modeling approach for ductile structural systems, consistent with the modeling assumptions and performance-based evaluation framework adopted in TBEC-2018. All buildings satisfied the Controlled Damage performance level defined in TBEC-2018.
Keywords: performance analysis; pushover analysis; reinforced-concrete frame structure